DISCRIMINACIÓN SOBRE TRABAJADORES DE TRABAJO TEMPORAL Y EMPLEADOS EN LA LEGISLACIÓN LABORAL BÚLGARA - Lazarova , Nikoleta (Revista Inclusiones, 2016)
With amendments and supplements to the Labor Code of June 2004, the Bulgarian legislator has taken steps in the direction of establishing common rights and obligations of workers and employees in an employment relationship arising from a contract of employment of any kind. Despite the desire to settle the maximum antidiscrimination protection to employees employed on fixed-term contracts, the existing labor legislation continues to contain provisions that could be classified as discriminatory. What is specific in these cases is that the discriminating subject is not the employer – it is the legislator. The article is an analysis of the provisions that have a discriminatory effect on employees and workers working under fixed-term contracts. The author makes relevant proposals de lege ferenda, aimed at overcoming shortcomings in labor laws that would lead to ensuring the application of the principle of non-discrimination.